Answer:
x=2
Step-by-step explanation:
y=3x+2
y=x+6
Since you're stating that, they both equal because equation is equated to equation 2 because of the Y.
Therefore, substitute into both equations as shown:
3x+2=x+6
3x-x=6-2 (bring 2 to the other side by subtracting 2 as well as x)
2x=4
2x/2=4/2 (dividing 2 on both sides to get rid off 2 in 2x)
x=2.
Answer:
x^2 + 3x -1
Step-by-step explanation:
f(x) = 3x-2
g(x) = x^2+1
(f+g)(x) = 3x-2+x^2+1
Combine like terms
= x^2 + 3x -1
Answer:
1) 15 feet per second
2) distance after 3 seconds 45 feet
3) slower
Step-by-step explanation:
1) 30/2 = 15
2) 15 x 3
3) 55/4 = 13.75 < 15